2013
DOI: 10.5114/fn.2013.39723
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evidence of the beneficial role of immune system cells in a rat model of surgical brain injury

Abstract: A b s t r a c t The blood-brain barrier prevents infiltration of peripheral immunocompetent cells into the CNS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…These mice had a worse recovery following injury, indicating that leukocyte trafficking of certain immune cells is beneficial in SCI [46]. In general, monocytes and macrophages are thought to have an essential role in restoring the functional integrity of the BCSFB by phagocytosing dismantled structural elements and extracellular debris in the injured CP, again implying that infiltrating leukocytes can have a beneficial function [47][48][49]. By contrast, invasion of inflammatory cells after ischemic injury or TBI can be detrimental to neuronal survival and functional recovery after injury, demonstrating the complexity of immune cell trafficking across the CP during various inflammatory conditions and the need for a specific therapeutic approach [8,[10][11][12].…”
Section: Dual Role Of Leukocyte Infiltrationmentioning
confidence: 96%
“…These mice had a worse recovery following injury, indicating that leukocyte trafficking of certain immune cells is beneficial in SCI [46]. In general, monocytes and macrophages are thought to have an essential role in restoring the functional integrity of the BCSFB by phagocytosing dismantled structural elements and extracellular debris in the injured CP, again implying that infiltrating leukocytes can have a beneficial function [47][48][49]. By contrast, invasion of inflammatory cells after ischemic injury or TBI can be detrimental to neuronal survival and functional recovery after injury, demonstrating the complexity of immune cell trafficking across the CP during various inflammatory conditions and the need for a specific therapeutic approach [8,[10][11][12].…”
Section: Dual Role Of Leukocyte Infiltrationmentioning
confidence: 96%
“…Previous histologic analysis of malignant glioma reveals TAMs composed of microglia, monocytes/macrophages, astrocytes, endothelial cells, neural stem/progenitor cells, pericytes, and other immune cell infiltrates (34). Under pathological conditions, peripheral monocytes can enter the CNS from the blood through a disrupted blood brain barrier, and further showing a tendency to richer than oligodendrocytes (35,36). To our best knowledge, glioma TAMs can come from tissue-resident macrophages or macrophages recruited from blood, and these macrophages account for 30-50% of the tumor mass (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Although remarkable neurosurgical advances have been achieved in the management of brain tumors [2], movement disorders [3], and neurologic injury [4], these procedures can result in unavoidable secondary trauma to the adjacent, non-diseased brain structures. Studies have demonstrated that physical insults to the brain can initiate a cascade of neurocognitive changes that result in long-term neurodegeneration and brain atrophy [5]. However, the cause-and-effect association of such acute and delayed cognitive and/or neurological deficits is often obscured by the substantial potential of the brain for compensatory changes, the long human lifespan, and aging-related phenomena.…”
Section: Cognitive/behavioral Deficitsmentioning
confidence: 99%
“…
Neurosurgical and Neurological Residuals of
Cognitive/Behavioral DeficitsAlthough remarkable neurosurgical advances have been achieved in the management of brain tumors [2], movement disorders [3], and neurologic injury [4], these procedures can result in unavoidable secondary trauma to the adjacent, non-diseased brain structures. Studies have demonstrated that physical insults to the brain can initiate a cascade of neurocognitive changes that result in long-term neurodegeneration and brain atrophy [5]. However, the cause-and-effect association of such acute and delayed cognitive and/or neurological deficits is often obscured by the substantial potential of the brain for compensatory changes, the long human lifespan, and aging-related phenomena.The increased national and global burden of brain and other central nervous system diagnoses has highlighted the necessity for continuity of care to improve function and the quality-of-How to cite this article: Robert B S. The Integration and Application of Neuropsychology into the Treatment and Care of Patients with Brain Conditions.
…”
mentioning
confidence: 99%